New aspect of studying the mechanisms of development of the lungs ventilation capacity disorders in children with bronchial asthma - Shumna, T. Ye.; Fedosieieva, O. S.; Kamyshnyi, A. M.; Шумна, Таміла Євгенівна; Федосєєва, Олена Станіславівна; Камишний, Олександр Михайлович; Шумная, T. Е.; Федосеева, O. С.; Kaмышный, А. M. (My University, 2020)
Study of the pathogenetic role of the polymorphism of the ACTN3 gene (actinin, alpha 3) rs1815739 in the development of lungs ventilation capacity disorders in children with bronchial asthma.Materials and methods. To study the polymorphism of ACTN3 gene (actinin, alpha 3) rs1815739, the molecular and genetic study of 90 children aged from 6 to 18 years with bronchial asthma, who were passing in-patient treatment at the Allergy Department of the Municipal NonProfit Enterprise "Children's Hospital no.5" of Zaporizhia City Council, and 25 healthy children (control group) was conducted. The external respiration function was studied using a computer spirograph "PULMOREM" TU U 33.1-02066769-005-2002 (Kharkiv). The study of the polymorphism of the ACTN3 gene (actinin, alpha 3) rs1815739 was performed in the Division of Molecular Genetic Researches of the Training Medical Laboratory Center at the Department of Microbiology of Zaporizhia State Medical University in Zaporizhia on the CFX96TM Real-Time PCR Detection Systems amplifier (Bio-Rad laboratories Inc., USA) with extraction of DNA from venous blood by means of polymerase-chain reaction. The results of the study were processed using statistical analysis of the license software package Statistica for Windows 6.1.RU, serial number AXXR712D833214SAN5. Results. The study of the distribution of allelic genes and genotypes of ACTN3 (actinin, alpha 3) polymorphism for rs1815739 showed that among children with bronchial asthma, the homozygous C/C genotype was recorded in 37.7% of cases, heterozygous C/T genotype in 40% of cases, homozygous T/T genotype in 22.3% of cases, while in healthy children, the frequencies of the homozygous C/C (68%) and T/T (4%) genotypes were significantly more frequent. The indicators of external respiration function (forced vital capacity (FVC), forced expiratory volume at the 1-second (FEV1)) in patients with a homozygous C/C genotype were significantly lower than in patients with homozygous T/T genotype and were 2.69 (1.9; 3.49) vs. 3.11 (2.47; 4, 14) and 2.06 (1.6; 2.76) vs. 2.82 (2.02; 3.51). The patency of large and small bronchi, characterized by spirographic MEF25 and MEF75 indicators, was significantly better in children with bronchial asthma with homozygous T/T genotype than in children with C/T and C/C genotypes (5.46 (4.87; 6, 31) and 2.36 (1.89; 3.32) against 4.54 (3.69; 5.43) and 4. 17 (3.24; 5.44), and 1.88 (1.10; 2.56) and 1.69 (1.16; 2.02), respectively. In children with bronchial asthma and the C/C and C/T genotypes of ACTN3 gene (actinin, alpha 3) rs1815739 with probable sufficient synthesis of alpha-actinin-3 protein in muscles, a stronger contraction of the respiratory muscles on inhalation is possible, and in patients with the T/T genotype, which encodes insufficient synthesis of alpha-actinin-3 protein in the muscles, the muscle contraction is probably less pronounced in asthma attacks, which can lead to less pronounced disorders of lungs ventilation capacity. Conclusions. The study of ACTN3 (actinin, alpha 3) rs1815739 gene polymorphism showed that the C / C and C / T genotypes were associated with impaired lung ventilation in children with bronchial asthma. Дослідження патогенетичної ролі поліморфізму гена АCTN3 (actinin, alpha 3) rs1815739 в розвитку порушень вентиляційної здатності легень у дітей з бронхіальною астмою. Матеріали і методи. Для вивчення поліморфізма гена АCTN3 (actinin, alpha 3) rs1815739 було проведено молекулярно-генетичне дослідження 90 дітей з бронхіальною астмою від 6 до 18 років, які перебували на стаціонарному лікуванні в алергологічному відділенні Комунального неприбуткового підприємства «Дитяча лікарня №5» Запорізької міської ради та 25 здорових дітей (контрольна група). Функція зовнішнього дихання досліджувалась з використанням комп´ютерного спірографа «PULMOREM» ТУ У 33.1- 02066769-005-2002 (м.Харків). Вивчення поліморфізму гена АCTN3 (actinin, alpha 3) rs1815739 проводилось у відділі молекулярно-генетичних досліджень навчального медиколабораторного центра на кафедрі мікробіології Запорізького державного медичного університету, м. Запоріжжя, на ампліфікаторі CFX96TM Real-Time PCR Detection Systems («Bio-Rad laboratories, Inc.», USA) з виділенням ДНК із венозної крові за допомогою полімеразно-ланцюгової реакції. Отримані результати дослідження були оброблені за допомогою статистичного аналізу лицензійного пакета програм Statistica for Windows 6.1.RU, cерійний номер АХХR712D833214SAN5. Результати. Досліджння розподілу алельних генів та генотипів поліморфізма АCTN3 (actinin, alpha 3) rs1815739 показало, що серед дітей з бронхіальною астмою, гомозиготний генотип С/С реєструвався в 37,7% випадках, гетерозиготний генотип С/Т - у 40%; гомозиготний генотип Т/Т – у 22,3% обстежених, в той час як у здрових дітей частоти гомозиготних генотипів С/С (68%) та Т/Т (4%) зустрічались достовірно частіше. Показники функції зовнішнього дихання (форсована життєвої ємність легень (FVC), об'єм форсованого видоху за першу секунду (FEV1)) у пацієнтів з гомозиготним генотипом C/C були достовірно нижчими, ніж у пацієнтів з гомозиготним генотипом Т/Т і склали 2.69 (1.9;3.49) проти 3,11 (2,47;4, 14) та 2.06 (1.6;2.76) проти 2.82 (2.02;3.51). Прохідність крупних та мілких бронхів, що характеризувалась спірографічними показниками MEF25 та MEF75, була достовірно кращою у дітей з бронхіальною астмою з гомозиготним генотипом Т/Т, ніж у дітей з генотипами С/Т та С/С (5.46 (4.87;6,31) і 2.36 (1.89; 3.32) проти 4.54 (3.69;5.43) і 4. 17 (3.24; 5.44) та 1.88 (1.10; 2.56) і 1.69 (1.16;2.02), відповідно. У дітей з бронхіальною астмою з генотипами С/С і С/Т гена АCTN3 (actinin, alpha 3) rs1815739 з імовірним достатнім синтезом білка альфа-актиніну-3 у м'язах, можливе більш сильне скорочення дихальних м'язів при вдихуванні повітря, а у пацієнтів із генотипом Т/Т, який кодує недостатній синтез білка альфа-актиніну-3 у м'язах, при приступі ядухи скорочення м'язів імовірно менш виражене, що може призводити до менш виражених порушень вентиляційної здатності легень. Висновки. Дослідження поліморфізма гена АCTN3 (actinin, alpha 3) rs1815739 показало, що генотипи С/С та С/Т були асоційовані з порушеннями вентиляційної здатності легень у дітей з бронхіальною астмою. Изучение патогенетической роли полиморфизма гена АCTN3 (actinin, alpha 3) rs1815739 в развитии нарушений вентиляционной способности легких у детей з бронхиальной астмой. Материалы и методы. Для изучения полиморфизма гена АCTN3 (actinin, alpha 3) rs1815739 было проведено молекулярно-генетическое исследование 90 детей с бронхиальной астмой от 6 до 18 лет, которые находились на стационарном лечении в аллергологическом отделении Коммунального неприбыльного предприятия «Детская больница №5» Запорожского городского совета и 25 здоровых детей (контрольная группа). Функция внешнего дыхания исследовалась с использованием компьютерного спирографа «PULMOREM» ТУ У 33.1-02066769-005-2002 (м.Харків). Изучение полиморфизма гена АCTN3 (actinin, alpha 3) rs1815739 проводилось в отделе молекулярно-генетических исследований ученого медико-лабораторного центра на кафедре микробиологии Запорожского государственного медицинского университета, г. Запорожье, на амплификаторе CFX96TM Real-Time PCR Detection Systems («Bio-Rad laboratories, Inc.», USA) с выделением ДНК из венозной крови при помощи полимеразно-цепной реакции. Полученные результаты исследования были обработаны при помощи статистического анализа лицензионного пакета программ Statistica for Windows 6.1.RU, cерійний номер АХХR712D833214SAN5. Результаты. Изучение распределения аллельных генов и генотипов полиморфизма АCTN3 (actinin, alpha 3) rs1815739 показало, что среди детей с бронхиальной астмой, гомозиготный генотипом С/С регистрировался в 37,7% случаях, гетерозиготный генотип С/Т - у 40%; гомозиготный генотип Т/Т – у 22,3% обследованных, в то время как у здровых детей частоты гомозиготных генотипов С/С (68%) и Т/Т (4%) встречались достоверно чаще. Показатели функции внешнего дыхания (форсированная жизненная емкость легких (FVC), объем форсованного выдоха за перую секунду (FEV1)) у пациентов с гомозиготным генотипом C/C были достоверно ниже, чем у пациентов с гомозиготным генотипом Т/Т и составили 2.69 (1.9;3.49) против 3,11 (2,47;4, 14) и 2.06 (1.6;2.76) против 2.82 (2.02;3.51). Проходимость крупных и мелких бронхов, которая характеризовалась спирографическими показателями MEF25 и MEF75, была достоверно лучшей у детей с бронхиальной астмой с гомозиготным генотипом Т/Т, чем у детей с генотипами С/Т и С/С - (5.46 (4.87;6,31) и 2.36 (1.89; 3.32) против 4.54 (3.69;5.43) и 4. 17 (3.24; 5.44); 1.88 (1.10; 2.56) и 1.69 (1.16;2.02), соответственно. У детей с бронхиальной астмой с генотипами С/С и С/Т гена АCTN3 (actinin, alpha 3) rs1815739 с вероятным достаточным синтезом белка альфа-актинина-3 в мышцах, возможно более сильное сокращение дыхательных мышц на вдохе, а у пациентов с генотипом Т/Т, кодирующим недостаточный синтез белка альфаактинина-3 в мышцах, при приступе удушшя сокращения мышц вероятно менее ввражено, что может приводить к менее выраженным нарушениям вентиляционнй способности легких. Выводы. Изучение полиморфизма гена АCTN3 (actinin, alpha 3) rs1815739 показало, что генотипы С/С и С/Т были асоциированы с нарушениями вентиляционной способности легких у детей с бронхиальной астмой.
Новий аспект дослідження механізмів розвитку порушень вентиляціної здатності легень у дітей з бронхіальною астмою
Новий аспект изучения механизмов развития нарушений вентиляцинной способности легких у дітей с бронхиальной астмой
Keywords: gene; polymorphism; alpha-actinin-3; bronchial asthma; lungs ventilation capacity; children; ген; поліморфізм; альфа-актинін-3; бронхіальна астма; вентиляційна здатність легень; діти; ген; полиморфизм; альфа-актинин-3; бронхиальная астма; вентиляционная способность легких; дети